RETRACTED: Assessing the Role of Green Finance and Education as New Determinants to Mitigate Energy Poverty - Hou, Ruirui; Du, Lijie; Khan, Syed Abdul Rehman; Razzaq, Asif; Ramzan, Muhammad (Frontiers in Psychology, 2022)
Energy poverty (EP) is a problem that affects developed and developing economies, and its mitigation is of great significance to social welfare. EP affects Latin American countries as well, and policymakers have recently attempted to address this issue, particularly in the aftermath of the recent economic crisis. It is essential to measure and evaluate EP in order to effectively implement strategies and policies. Using a panel quantile regression approach, we investigate the heterogeneous impact of green finance, renewable energy and energy efficiency (EE) on EP for 33 Latin American countries over the period 2000-2018. Furthermore, certain associated control variables are incorporated in our model to avoid an omitted variable bias. According to empirical results, the impact of independent variables on EP is heterogeneous. Specifically, green finance is an important source of alleviating EP and it has a significant positive effect across all quantiles, but it is especially strong at the middle quantiles. Renewable energy and energy efficiency significantly mitigate energy poverty with the strongest effects occurring at higher quantiles. By including green finance, renewable energy and energy efficiency as main explanatory determinants of enery poverty, the findings urge policymakers in Latin American countries to design a comprehensive energy conservation policy to minimise the effects of massive energy poverty.